Gestational weight gain and its determinants among pregnant women attending antenatal care at West Shawa Hospitals, Oromia, Ethiopia - Teka Girma Terfassa; Dessalegn Wirtu; Gudina Egata (PLoS ONE, 2025)
Background Gestational Weight Gain (GWG) is a crucial factor influencing maternal and neonatal health outcomes. Identifying the determinants of GWG can help develop targeted interventions to improve pregnancy outcomes. Objective This study aimed to assess the magnitude of gestational weight gain and identify its determinants among pregnant women attending antenatal care (ANC) services at West Shoa Hospital, Ethiopia, in 2024. Methodology A bidirectional cohort study was conducted among 885 pregnant women attending antenatal care (ANC) services at West Shoa Hospitals, Ethiopia, before 12 weeks of gestation. Data were collected through face-to-face interviews using the CesPro application and document review. The determinants of GWG were analyzed using an ordinal logistic regression model, assuming the proportional odd assumptions. The Brant test was used to determine whether the parallel assumption was held. The STATA “ologit” command was used for ordinal regression, and the “brant” test was applied to verify the validity of the model. Odds ratios (OR) with 95% confidence intervals (CI) were estimated, and statistical significance was declared at p < 0.05. Results Approximately 69% of pregnant women experienced insufficient weight gain, 26% had adequate weight gain, and 5% had excessive weight gain during pregnancy. Pre-pregnancy Body Mass Index was a significant determinant of gestational weight gain. Compared to underweight women, overweight women had 10.58 times higher odds (95% CI: 5.24–21.37) of being in a higher weight gain category, while obese women had 10.64 times higher odds (95% CI: 1.87–60.57) of achieving normal or excessive gestational weight gain. Partner education significantly influenced gestational weight gain, with those who could only read and write having 0.22 times lower odds (95% CI: 0.05–0.98) of excessive weight gain compared to those with higher education. Maternal occupation also played a role, as daily laborers had 0.26 times lower odds (95% CI: 0.08–0.87) of adequate weight gain than employed women. The normal hemoglobin category was associated with increased odds of being in a higher weight gain category (adequate or excessive) compared to a lower category, with an odds ratio (OR) of 1.04 (95% CI: 1.01–1.08). Conversely, alcohol consumption was associated with lower odds of being in a higher weight gain category, with an OR of 0.49 (95% CI: 0.25–0.99), suggesting that alcohol drinkers had lower odds of experiencing normal or excessive weight gain compared to non-drinkers. Conclusion A significant proportion of pregnant women experienced inadequate gestational weight gain. Pre-pregnancy BMI, partner’s educational status, maternal occupation, hemoglobin levels, and alcohol consumption were key determinants of gestational weight gain. These findings highlight the need for targeted nutritional counseling and lifestyle interventions to promote optimal weight gain during pregnancy.